Projeto do sistema de elevação por parafuso de potência para uma esteira transportadora de comprimento ajustável - SOUZA, Thais Cristina Barbosa (2022)
This work aims to solve the problem of manual activity of lifting and moving products, presenting as a solution the design of a lifting and tilting system for a conveyor belt of adjustable length, capable of supporting small to medium-sized products, enabling the supply and/or shortage of trucks without having a major impact on the health of employees. Based on analysis of mechanical design methodologies, possible lifting and cargo handling systems that could meet the project's requirements were evaluated. Among the proposed options, the lifting system by power screw with Acme thread was chosen, in which it has greater gain in cost and benefit for the project, the inclination of the equipment, also with this same vision, was defined by an intermediate bar with length smaller. The work consisted of the study and sizing of the power screw, selection of the electric geared motor and the calculation of forces acting on the structural elements using the Finite Element Method (FEM), using computer analysis software.